HIV-positive pregnant women and non-breastfeeding: an epidemiological study (Research, Society and Development, 2022)
Objective: To analyze the epidemiological profile of HIV-infected pregnant women who will be unable to breastfeed in Brazil. Methods: Refers to a retrospective, epidemiological, quantitative study. The sample was composed of all cases of HIV-positive pregnant women notified between 2017 and 2021. The data exposed throughout the study were extracted from SINAN and SINASC inserted in DATASUS. Results: In the last five years, there were 36,792 positive pregnant women in Brazil. Rio Grande do Sul and its capital, Porto Alegre, is the place with the highest incidence of pregnant women with HIV, the capital reaching a rate of 17.1 cases/thousand live births. The range of 20 to 24 years old had more seropositive pregnant women in the last five years, regarding schooling, the highest percentage was among pregnant women with complete secondary education. According to race/color, there is a predominance of cases of HIV infection among brown pregnant women. Conclusion: In order for there to be a reduction in vertical transmission rates, it is necessary to raise awareness among pregnant women through health professionals when performing prenatal care. In the post partum period, guidance should be given on non-adherence to breastfeeding, as it is contraindicated in HIV-positive pregnant women.